challenges to grant of injunction pending appeal in Nigeria – way out (2013)
This paper examined the conditions for the grant of Order of Injunction Pending Appeal by Nigerian Courts. The paper traced the origin of the Order from the English authorities, and the adoption into the Nigerian judicial system. The author examined the High Court of Lagos State Rules and the Federal High Court Rules to establish the procedural source of the application of the Injunction Pending Appeal by the Courts and concluded that the rules do not support the Order. The confusion by the Courts in associating the conditions for the grant of Interlocutory Injunction and Injunction Pending Appeal was critically examined. The proper and acceptable conditions for the grant of the Order as laid down recently by the Supreme Court and a call for liberal application of the conditions by the Court as well as a suggestion for a change in the nomenclature concludes the paper.